Identification of a Consolidation Phase in Immunological Memory - Mantile, Francesca; Capasso, Angelo; De Berardinis, Piergiuseppe; Prisco, Antonella (Frontiers in Immunology, 2019)
Long lasting antibody responses and immunological memory are the desired outcomes of vaccination. In general, multiple vaccine doses result in enhanced immune responses, a notable exception being booster-induced hyporesponsiveness, which has been observed with polysaccharide and glycoconjugate vaccines. In this study, we analyzed the effect of early booster doses of multimeric protein vaccine (1-11)E2 on recall memory to B epitope 1-11 of β-amyloid. Mice immunized with a single dose of (1-11)E2 stochastically display, when immunized with a recall dose 9 months later, either memory, i.e. an enhanced response to epitope 1-11, or hyporesponsiveness, i.e a reduced response. Memory is the most common outcome, achieved by 80% of mice. We observed that a booster dose of vaccine (1-11)E2 at day 15 significantly reduced the ratio between the magnitude of the secondary and primary response, causing an increase of hyporesponsive mice. This booster-dependent disruption of recall memory only occurred in a limited time window: a booster dose at day 21 had no significant effect on the ratio between the secondary and primary response magnitude. Thus, this study identifies a consolidation phase in immunological memory, that is a time window during which the formation of memory is vulnerable, and a disrupting stimulus reduces the probability that memory is achieved.